The relationship between managerial overconfidence with basic metals firms value - Dashtbayaz, Mahmoud Lari; Mohammadi, Shaban (International Journal of Accounting and Economics Studies, 2016)
The purpose of the present study is to investigate the relationship between Managerial overconfidence and Basic metals firm value of the listed companies on the Tehran Stock Exchange (TSE).The population includes 25 firms selected through systematic sampling. The data is collected from the audited financial statements of the firms provided by TSE’s website from 2010 to 2015. In this study the variables, Overconfidence based on earning per share (OEPS), Overconfidence based on capital cost (OCC) has been used to investigate Managerial overconfidence. The results of multiple linear regression analysis show that there is a significant relationship between Overconfidence based on earning per share (OEPS) and firm value. In addition, there is a significant relationship between Overconfidence based on capital cost (OCC) and firm value. The present research examined the relationship between Managerial overconfidence and Basic metals firm’s value of the Basic metals firms listed in Tehran Stock Exchange. The results of multivariate regression accepted two the hypotheses of the research. There is a significant relationship between Managerial overconfidence and Basic metals firm value.